Assessment of the Effect of Agricultural Site on the Biochemical Traits of Date Palm (Phoenix dactylifera L.) Offshoots of Halawi and Sayer Cultivars - Tuaema, Mohammed Hadi (Basrah Journal Of Date Palm Research, 2025)
This experiment was conducted during the 2024 growing season at three locations in Basrah Governorate (Abu Al-Khasib, Al-Hartha, and Al-Zubair) to study the effect of agricultural site on the pigment and carbohydrate contents in the leaves of two date palm (Phoenix dactylifera L.) cultivars, Halawi and Sayer. The results showed that the cultivation site significantly affected the contents of chlorophyll a, chlorophyll b, total chlorophyll, and carbohydrates in the leaves of both cultivars. The Halawi cultivar grown in Al-Hartha exhibited the highest contents of chlorophyll a (1.64 mg·g⁻¹), chlorophyll b (0.65 mg·g⁻¹), total chlorophyll (2.20 mg·g⁻¹), and carbohydrates (6.95 mg·g⁻¹), followed by the Al-Zubair site with values of 1.57, 0.53, 2.10, and 7.06 mg·g⁻¹, respectively. In contrast, the lowest values for these traits were recorded at the Abu Al-Khasib site (1.06, 0.32, 1.36, and 6.19 mg·g⁻¹, respectively). Regarding the Sayer cultivar, the highest carbohydrate content was observed at Al-Zubair and Al-Hartha (7.86 and 7.53 mg·g⁻¹, respectively), while the lowest value was recorded at Abu Al-Khasib (7.05 mg·g⁻¹). However, this cultivar showed the lowest concentrations of chlorophyll a, chlorophyll b, and total chlorophyll at the Al-Hartha site (0.85, 0.30, and 1.18 mg·g⁻¹, respectively). As for carotenoid content, the results indicated no significant differences among sites or between the two cultivars